Chaenothecopsis schefflerae (Ascomycota: Mycocaliciales): a widespread fungus on semi-hardened exudates of endemic New Zealand Araliaceae. Issue 4 (2nd October 2017) - Beimforde, Christina; Tuovila, Hanna; Schmidt, Alexander R.; Lee, William G.; Gube, Matthias; Rikkinen, Jouko
ABSTRACT: Ascomycetes specialised to live on hardened plant exudates occur worldwide, but the number of species so far described is relatively small (c.30). Particularly within the genus Chaenothecopsis (Ascomycota: Mycocaliciales), many species produce their ascomata on hardened but still relatively fresh outpourings of conifer resin or angiosperm exudate. Temperate rainforests of New Zealand provide habitat for several endemic Chaenothecopsis species, including Chaenothecopsis schefflerae, which was previously known from a single sample collected from the exudate of Schefflera digitata (Araliaceae) in the early 1980s. Here we show that C. schefflerae is neither lost nor very rare, but occurs sporadically throughout New Zealand. The fungus does not primarily grow on Schefflera but on exudate of several species of Pseudopanax (Araliaceae), also endemic to the region. We compare the morphology of the new specimens to the type specimen of C. schefflerae and provide a detailed description of the new material. Phylogenetic analyses based on nuclear ITS and LSU rDNA place C. schefflerae together with other morphologically similar Chaenothecopsis species growing on angiosperm exudates.